Digital communication and agency - Jakub Siwak (Communicare)
The recent Cambridge Analytica scandal, in which personally distinguishable information was collected without explicit permission from millions of Facebook users, once more brought into focus the potential dangers of our now-pervasive social media use. What the scandal primarily indicates is the unsettling idea that one’s personal information and what it reveals is open to an infrastructure capable of manipulating such information to its own ends. Despite such developments, in my experience of lecturing digital communication to students at a South African university, there is a lack of awareness of how the technical infrastructures that makes up digital communication can play a role in potentially negating our agency when using digital forms of communication. And this lack of awareness is echoed in the lax global response to the Cambridge Analytica scandal. In response, this article argues that digital space may well be antithetical to the notion of agency through digital communication. To do so, it turns to a very specific source; the post-structural theorist, Gilles Deleuze, and his conception of digital societies of control, as well as contemporary theoretical works that reflect his concerns over our agency within the virtual spaces we now increasingly inhabit.